Adsorbed Water Promotes Chemically Active Environments on the Surface of Sodium Chloride - Xiangrui Kong (1714498) (2023)
Gas–particle interfaces are chemically active environments. This study investigates the reactivity of SO2 on NaCl surfaces using advanced experimental and theoretical methods with a NH4Cl substrate also examined for cation effects. Results show that NaCl surfaces rapidly convert to Na2SO4 with a new chlorine component when exposed to SO2 under low humidity. In contrast, NH4Cl surfaces have limited SO2 uptake and do not change significantly. Depth profiles reveal transformed layers and elemental ratios at the crystal surfaces. The chlorine species detected originates from Cl– expelled from the NaCl crystal structure, as determined by atomistic density functional theory calculations. Molecular dynamics simulations highlight the chemically active NaCl surface environment, driven by a strong interfacial electric field and the presence of sub-monolayer water coverage. These findings underscore the chemical activity of salt surfaces and the unexpected chemistry that arises from their interaction with interfacial water, even under very dry conditions. Other Information Published in: The Journal of Physical Chemistry Letters License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1021/acs.jpclett.3c00980